Prenatal screening and diagnosis in multiple pregnancies. Issue 10 (October 2021) - Gent, Joanna; Navaratnam, Kate; Sharp, Andrew
Abstract: Multiple pregnancies account for 1.5% of pregnancies in the UK and both aneuploidies and structural anomalies occur more frequently in twins, compared to singletons. Comprehensive, individualised counselling is key in these challenging situations, requiring clinicians to communicate their knowledge of prenatal screening effectively. Prenatal screening and diagnosis is not straightforward in multiple pregnancies with variable performance of screening tests, choices to be made on diagnostic techniques and sampling, limited robust data on procedure-related risks and potentially complex decision-making in light of results. In this article we will address these issues and provide an up-to-date evidence summary derived from national guidance and published literature.